A Study to Examine the Association of Health Related Behaviours and Body Mass Index among Young Adults at Selected Colleges in Kancheepuram District, Tamil Nadu, India (Medico Legal Update, 2020)
A observational study to examine the association of Health related behaviours and Body mass index amongyoung adults at selected colleges in Kanchipuram District, Tamil Nadu, India’’. The objectives were toexamine the lifestyle practices and Body mass index among young adults at Kanchipuram district, TamilNadu and to find out the association between lifestyle practices and BMI with demographic variables. Theconvenience sampling was used to select 100 young adults. The data collection tools were validated andreliability was established. The data were collected by self-administered questionnaire. The collected datawas Tabulated and Analyzed. Descriptive and Inferential statistical methods were used. The study showsthat of the higher frequency of 18-24 years (96%) and lower frequency of 20-24 years (4%). In Gender, Maleis lowest frequency (28%) and Female is the highest frequency (72%). There was significant associationbetween the knowledge and the selected demographic variables.